Enhancement of Learning Outcomes Through Implementation of Best Practices in Teaching Learning Process: A Case Study - Ganesh, K. E.; Pranesha, T. S. (Journal of Engineering Education Transformations, 2018)
Learning outcomes of students are very important for the success of every class. Student’s mind at entry level to first year Engineering course is a mixture of so many thoughts; as students come from various social and psychological backgrounds. In the present study we have made an attempt to eliminate the psycho-logical barriers of the mind of the student with parental affection and friendly behaviour from the teacher side and simultaneously implementing some of the best teaching learning practices. With the implementation of above said ideas, we have observed that the class average marks of students have increased from the first (test-1) to third (test-3) assessment by about 24%. Also, about 75% of the students acquired grades A and B indicating a reasonably good performance at the semester end exams. A detailed case study of this episode is the subject matter of this paper.